Coupling hCG-based protease sensors with a commercial pregnancy test strip for simple analyses of protease activities - Park, Hyeon Ji; Kim, Yuseon; Lee, Kyung Won; Gwon, Minji; Yoon, Hyun C.; Yoo, Tae Hyeon (Biosensors and Bioelectronics, 2023)
Proteases play an essential role in many cellular processes, and consequently, abnormalities in their activities are related to various diseases. Methods have been developed to measure the activity of these enzymes, but most involve sophisticated instruments or complicated procedures, which hampers the development of a point-of-care test (POCT). Here, we propose a strategy for developing simple and sensitive methods to analyze protease activity using commercial pregnancy test strips that detect human chorionic gonadotropin (hCG). hCG was engineered to have site-specific conjugated biotin and a peptide sequence, which can be cleaved by a target protease, between hCG and biotin. hCG protein was immobilized on streptavidin-coated beads, resulting in a protease sensor. The hCG-immobilized beads were too large to flow through the membrane of the hCG test strip and yielded only one band in the control line. When the peptide linker was hydrolyzed by the target protease, hCG was released from the beads, and the signal appeared in both the control and test lines. Three protease sensors for matrix metalloproteinase-2, caspase-3, and thrombin were constructed by replacing the protease-cleavable peptide linker. The combination of the protease sensors and a commercial pregnancy strip enabled the specific detection of each protease in the picomolar range, with a 30-min incubation of the hCG-immobilized beads and samples. The modular design of the protease sensor and simple assay procedure will facilitate the development of POCTs for various protease disease markers.
Keywords: Control lines; Human chorionic gonadotrophins; Peptide linkers; Point of care; Point-of-care test; Pregnancy test strip; Pregnancy tests; Protease; Protease activities; Test strips; Biosensing Techniques; Biotin; Chorionic Gonadotropin; Endopeptidases; Female; Humans; Matrix Metalloproteinase 2; Peptide Hydrolases; Pregnancy; Pregnancy Tests; Human chorionic gonadotropin; Point-of-care test; Pregnancy test strip; Protease